Insights into the full-length SRPK2 structure and its hydrodynamic behavior - Alves Barbosa, Everton de Almeida; Seraphim, Thiago Vargas; Gandin, Cesar Augusto [UNESP]; Teixeira, Leilane Ferreira; Goncalves da Silva, Ronni Anderson; Righetto, Germanna L.; Goncalves, Kaliandra De Almeida; Vasconcellos, Raphael de Souza; Almeida, Marcia Rogeria; Silva Junior, Abelardo; Rangel Fietto, Juliana Lopes; Kobarg, Jorg; et al. (Elsevier B.V., 2019)
The serine/arginine-rich protein kinase 2 (SRPK2) has been reported as upregulated in several cancer types, with roles in hallmarks such as cell migration, growth, and apoptosis. These findings have indicated that SRPK2 is a promising emerging target in drug discovery initiatives. Although high-resolution models are available for SRPK2 (PDB 2X7G), they have been obtained with a heavily truncated recombinant protein version (-50% of the primary structure), due to the presence of long intrinsically unstructured regions. In the present work, we sought to characterize the structure of a full-length recombinant version of SRPK2 in solution. Low-resolution Small-Angle X-ray Scattering data were obtained for both versions of SRPK2. The truncated Delta N Delta S-SRPK2 presented a propensity to dimerize at higher concentrations whereas the full-length SRPK2 was mainly found as dimers. The hydrodynamic behavior of the full-length SRPK2 was further investigated by analytical size exclusion chromatography and sedimentation velocity analytical ultracentrifugation experiments. SRPK2 behaved as a monomer-dimer equilibrium and both forms have an elongated shape in solution, pointing to a stretched-to closed tendency among the conformational plasticity observed. Taken together, these findings allowed us to define unique structural features of the SRPK2 within SRPK family, characterized by its flexible regions outside the bipartite kinase domain. (C) 2019 Published by Elsevier B.V.